Capture and Process Differences Between Ontologies - Felix Engel; Mark Vanin; Nenad Krdzavac (IEEE Access)
The Ontology Development Tracker (OnDeT) has been developed to facilitate the computation and interactive exploration of differences between multiple versions of a Git-hosted ontology throughout its temporal evolution. Existing tools focus primarily on pairwise comparisons, which limits the ability to analyze the entire evalutionary history of the ontology. OnDeT addresses this limitation by integrating three existing tools for pairwise comparisons between ontologies. Based on changes have been made to the ontology, the OnDeT tool captures and processes differences between different versions of the same ontology. A comprehensive user interface allows users to examine and explore differences in chronological order, as well as to explore specific differences based on a selected class name and dates. In addition, a semantic representation of these differences has been developed using the Provenance Ontology (PROV-O) specification. The OnDeT Knowledge Graph (KG) leverages this representation to provide a detailed semantic overview of all differences. OnDeT is integrated into the Technische Informationsbibliothek (TIB) Terminology Service (TS). Finally, to validate its correctness, OnDeT was evaluated using reasoners and a series of competency questions.